Cost and return of Nara Batik Group’s Batik Fabrics Narathiwat Metropolis - Sudinpreeda, Haida (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
DOI:10.14456/pnuhuso.2023.11 This qualitative research was aimed to study the production procedure of batik fabric under the administration of Nara Batik Group and to study its cost and return fund. The study’s informants included the chairman and seven committee members. Structured interview was employed as the instrument. Data obtained was descriptively analyzed looking for percentage, cost, revenue, gross profit. The results showed that batik fabrics produced by the Group can be divided into 2 types: block-printed batik and hand-printed batik. An average cost of producing block-printed batik is 175.20 THB per yard, while that of hand-printed batik is 264.22 THB. Most of the production costs are spent for raw materials and fabric paints. The average monthly gross profit is 42,227 THB. The gross profit from the production of block-printed batik is higher than that of hand-printed batik, at 38,360 THB. The analysis of both gross profits revealed that the production of block-printed batik offers higher rate of return than the production of hand-printed batik. However, the Group still keeps the production of the latter continue and develops its craftsmanship to boost up the sale with addition to promote the community economy. Moreover, the traditional hand-printed batik, which requires the application of local wisdom, is popular among conservatives. In addition, this finding would be an approach to reduce cost of production and increase profits for the enterprises of the same profession.